SISTEM INFORMASI PENJADWALAN PROYEK MENGGUNAKAN METODE PERT (PROGRAM EVALUATION AND REVIEW TECHNIQUE) DI CV. INFOTECHMEDIA - Yus Jayusman; Murlinah Murlinah; Ogi Rizki Fadillah (LPPM STMIK BANDUNG, 2022)
CV. Infotech Media is a national private company with legal entity which is engaged in website, desktop andandroid-based software development services. At the time of construction, projects often experience delays inproject completion due to several factors, namely in determining the estimated work time, the determination of theestimated work time often experiences discrepancies because the determination of the time estimate still uses roughestimates and ignores the possibility of optimistic and pessimistic times. In addition, there is no system thatcalculates which jobs should be prioritized and which jobs can be postponed for some time. Based on the problemsthat occur today, a project scheduling information system is needed at CV. Infotech Media. The method used tosolve this problem uses the Program Evaluation and Review Technique (PERT) method to calculate the right timeestimate and determine the critical path where there is work that is prioritized or cannot be postponed. Based onthe test results achieved, the project scheduling information system has been able to overcome the problems thatexist in the company, namely, calculating the right time estimate, providing information about the critical pathand making a schedule in the form of a Gantt Chart